Tinjauan Yuridis Penerapan Restortive Justice Terhadap Anak Pelaku Tindak Pidana Terorisme - Achmad Faisal Hasibuan; Lidia Rina Diahtaryani (Neolectura, 2026)
Terrorism is considered an extraordinary crime that poses serious threats to national security, public safety, and human rights. In several cases in Indonesia, acts of terrorism have involved children as perpetrators, creating a complex challenge within the criminal justice system. Children who commit criminal acts cannot be treated in the same manner as adults because they are still in a stage of psychological and social development. Therefore, a more humane and rehabilitative approach is required in addressing children in conflict with the law, including those involved in terrorism-related offenses. One of the approaches that can be applied is restorative justice, which emphasizes the restoration of relationships between offenders, victims, families, and the community rather than focusing solely on punishment. This research aims to analyze the juridical implementation of restorative justice for children involved in terrorism offenses in Indonesia and to examine the challenges encountered in its application. The research employs a normative legal method using statutory and case approaches. The data were obtained through library research involving legislation, legal doctrines, and court decisions related to terrorism cases involving children. The findings indicate that although Law Number 11 of 2012 concerning the Juvenile Criminal Justice System provides opportunities for restorative justice through diversion mechanisms, its implementation in terrorism cases remains limited. In practice, many court decisions still prioritize retributive punishment rather than rehabilitative measures. Therefore, strengthening the understanding of law enforcement officials and improving legal policies are necessary to ensure that restorative justice can be more effectively implemented within Indonesia’s juvenile criminal justice system.